Sifat Fisikokimia, Antioksidan, dan Sensori Infusa Herbal Daun Beluntas (Pluchea indica Less) dengan Penambahan Daun Kelor (Moringa oleifera Lam): Physicochemical, Antioxidant, and Sensory Properties of Herbal Infusion of Pluchea indica Less Leaf with Moringa oleifera Lam Leaf Addition - Widyawati, Paini Sri; Suseno, Thomas Indarto Putut; Budianta, Tarsisius Dwi Wibawa; Dyancandra, Gabriella Natasha; Nayottama, Ignasius Pamudji Anggaraksa (JURNAL AGROTEKNOLOGI, 2024)
Pluchea (Pluchea indica Less) leaf powder about 2 grams that was brewed in hot water at 95oC for 5 minutes resulted in herbal infusion with the highest panelist acceptance but low antioxidant activity compared to the other proportions in previous research. So that, it is necessary to add other herbs to increase antioxidant activity, i.e. moringa (Moringa oleifera Lam). This research aimed to determine the effect of moringa (Moringa oleifera Lam) leaves powder proportion to physicochemical, antioxidant, and sensory properties on pluchea (Pluchea indica Less) leaf powder infusion. The design of the research was a randomized block design (RBD) with a single factor, i.e. the proportions of pluchea and moringa leaves powder consisting of 7 treatment levels [100:0, 90:10, 80:20, 70:30, 60:40, 50:50, and 40:60 (%w/w) respectively]. The result showed that the proportion of moringa leaves powder significantly influenced the physicochemical and sensory properties of infusion. The higher proportion of pluchea leaf powder caused the increasing of moisture content, pH, lightness (L*), redness (a*), yellowness (b*), hue (oh), and chroma (C), but the decreasing of total acid and turbidity of pluchea leaf powder infusion. The improvement of pluchea leaf powder proportion significantly reacted on the bioactive compounds and antioxidant activities. The highest of the bioactive compounds and antioxidant activities were had of pluchea leaves powder infusion at 100:0 (%w/w) proportion of moringa leaves. Based on sensory analysis, the best treatment of pluchea leaf powder infusion was obtained at pluchea and moringa leaves proportion at 90:10 (%w/w) with 1.04 score. In the future, this formulation can be used as an alternative of herbal drink.  Keywords: infusion, leaf powder, physicochemical, pluchea indica less, sensory